Latino Orlando : Suburban Transformation and Racial Conflict - Delerme, Simone Pierre (Book collections on Project MUSE., 2020)
"Latino Orlando" portrays the experiences of first- and second-generation immigrants who have come to the Orlando metropolitan area from Puerto Rico, Cuba, Mexico, Venezuela, Colombia, and other Latin American countries. While much research on immigration focuses on urban destinations, Simone Delerme delves into a middle- and upper-class suburban context, highlighting the profound demographic and cultural transformation of an overlooked immigrant hub